Weed economic thresholds : Useful agronomic tool or pipe dream? - O’Donovan, J.T. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1996)
Interest in more rational and objective approaches to weed management has increased considerably in Canada and elsewhere. Cost/benefit issues, environmental concerns, and the development of weed resistance to herbicides have cast doubt on the rationality and sustainability of prophylactic herbicide use. The concept of an economic threshold for weeds and the broader concept of integrated weed management have considerable potential as practical agronomic tools in Canadian crop production Systems. A large number of experiments have been conducted to determine the impact of weeds on crop yield, but the models developed from these studies have been put to little practical use. Constraints to the practical implementation of these concepts include a lack of realistic sampling procedures to assess the impact of weeds on crops over large areas, and a lack of information on the long-term implications of seed production by uncontrolled weeds. Weed ecologists conducting weed interference experiments should define their objectives better, and should provide guidelines on how their findings can be used at the farm level. Emphasis should be placed on the effects of the crop on the weed rather than the weed on the crop. There is also a need for greater coordination of research activities among weed ecologists. The establishment of standard protocols for long-term studies across locations and years would enhance the relevance and precision of weed interference models, and lead to the development of user- friendly decision support Systems specifically adapted to aiding rational weed management decisions in Canadian crop production Systems. The development of such Systems will be essential to the implementation of weed thresholds and integrated weed management.